Playing games at the Library: Seriously? - Swiatek, Cécile; Gorsse, Myriam (LIBER Quarterly: The Journal of the Association of European Research Libraries, 2016)
During the past ten years, libraries have been developing gaming activities from library board games to mystery games and immersive roleplaying games. This article aims at giving a general overview of gaming issues in French academic libraries. General gaming theories are quickly reviewed, basic keys are given about how and why to set up a gaming service and department at the academic library, concrete and recent initiatives are presented. This article focuses on non-virtual and public-oriented games that were already organised in and by libraries. More generally, it underlines how to use gaming activities for promoting organisational innovation. It concludes on the necessity to settle a strategy for gaming activities, to enforce management practices, and on the importance to publicise the initiatives by establishing a public gaming policy and programme, and by formalising communication plans, staff training and knowledge management. The results of this fact study highlight how gaming activities are becoming a new reality for libraries, which requires a proper management perspective.